Environmental risks in the port of Huarmey - Cabrera Carranza, Carlos (2003)
This work evaluates the environmental risks resulting from the industrial fishing activity and mining activity (Antamina pipeline) in the port of Huarmey. This study is expected to contribute to the scientific knowledge of environmental risks, increase the quality of life of the population and protect the environment.